2016
DOI: 10.1128/aac.01251-16
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Antibiotics Active against Methicillin-Resistant Staphylococcus aureus Based on Activity in an Established Biofilm

Abstract: We used in vitro and in vivo models of catheter-associated biofilm formation to compare the relative activity of antibiotics effective against methicillin-resistant Staphylococcus aureus (MRSA) in the specific context of an established biofilm. The results demonstrated that, under in vitro conditions, daptomycin and ceftaroline exhibited comparable activity relative to each other and greater activity than vancomycin, telavancin, oritavancin, dalbavancin, or tigecycline. This was true when assessed using establ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 27 publications
0
34
0
2
Order By: Relevance
“…This is particularly true when the concentration of vancomycin present following irradiation (3.7 μg/ml) is viewed in the context of the breakpoint minimum inhibitory concentration (MIC) for vancomycin susceptibility (2.0 μg/ml). Moreover, previous studies from our group have demonstrated that concentrations this low have little to no effect on bacterial viability within the context of a biofilm [20]. Whether these relatively low concentrations are a function of a reduced capacity to load vancomycin or a reduced capacity to achieve its PT-mediated release is not clear, but it should be noted that vancomycin is also a relatively large antibiotic (Fig.…”
Section: Resultsmentioning
confidence: 91%
See 4 more Smart Citations
“…This is particularly true when the concentration of vancomycin present following irradiation (3.7 μg/ml) is viewed in the context of the breakpoint minimum inhibitory concentration (MIC) for vancomycin susceptibility (2.0 μg/ml). Moreover, previous studies from our group have demonstrated that concentrations this low have little to no effect on bacterial viability within the context of a biofilm [20]. Whether these relatively low concentrations are a function of a reduced capacity to load vancomycin or a reduced capacity to achieve its PT-mediated release is not clear, but it should be noted that vancomycin is also a relatively large antibiotic (Fig.…”
Section: Resultsmentioning
confidence: 91%
“…Moreover, the amount of antibiotic released in the absence of laser irradiation was <2 μg/ml, and our previous studies would suggest that this concentration is not effective in the context of an established S. aureus biofilm [20]. This suggests that the killing observed 24 hrs after exposure to the AuNC@Dap/PDA-aMntC formulation in the absence of laser irradiation may be due to some other factor.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations